2011
DOI: 10.1210/jc.2011-1286
|View full text |Cite
|
Sign up to set email alerts
|

The Fall in Leptin Concentration Is a Major Determinant of the Metabolic Adaptation Induced by Caloric Restriction Independently of the Changes in Leptin Circadian Rhythms

Abstract: Our results confirm an important role for leptin as an independent determinant of the metabolic adaptation in response to CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 26 publications
5
57
1
1
Order By: Relevance
“…In agreement with studies examining dietary-induced weight loss, 11,22,23 the compensatory downregulation in REE observed in the present study was associated with the change in fasting leptin following EX (independent of changes in FM). Baseline fasting leptin concentrations decreased by 13% during EX and this decline was related to the change in FM.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with studies examining dietary-induced weight loss, 11,22,23 the compensatory downregulation in REE observed in the present study was associated with the change in fasting leptin following EX (independent of changes in FM). Baseline fasting leptin concentrations decreased by 13% during EX and this decline was related to the change in FM.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to these results, the energy restriction induced change in leptin concentration was independently related to the adaptive response, indicating that a greater decrease in leptin correlates with, and could partly explain a greater disproportionate reduction in REE. Previously, leptin had been shown to be correlated to the weight loss induced decrease of REE [43,44]; our results specifically indicate a relation with adaptive thermogenesis, in line with Lecoultre et al [45]. Rosenbaum et al showed that leptin administration during a weight-reduced state returned energy expenditure to pre-weight loss levels [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…It seems that leptin reduction after prolonged caloric restriction is one of those metabolic adaptations, that can be prevented by leptin replacement [124]. In this context, leptin combined with a reduction of caloric intake seems to further maintain weight loss avoiding diet-induced compensatory metabolic adaptations, that induce resistance to weight loss [125]. An optimization of this approach has been to combine leptin administration with other molecules able to improve leptin sensitivity, in order to reinforce body weight loss, the so called "leptin sensitizers".…”
Section: Leptin In Therapy and Leptin Sensitizersmentioning
confidence: 99%